FAKTOR – FAKTOR YANG MEMPENGARUHI VOLUME PEMBIAYAAN PADA BANK UMUM SYARIAH - saebani saebani (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2015)
This research analyzes the factors that influence in islamic commercial Bank financing,among these factors are external factors that the BI rate,inflation while Internal factors used are third party funds (DPK) ,capital Adequacy Ratio that is so volatile That the economic situation is difficult for developing countries Indonesia ,this study aims to Determine how the influence of the BI rate,inflation ,Third Party Fund (DPK) ,capital adequacy Ratio (CAR) and the Non Performing Financing (NPF) agains Financing the Islamic Banks ,which occrrued between 2010 through 2014 .The result of this research are summarized in the Third Party Fund (DPK) ,Capital Adequacy Ratio (CAR) and the inflation effect on the financing ,while Non Performing Financing (NPF) and the BI Rate was not effect on the financing on islamic Banks.